Genotype and Haplotype of Interleukin-17F (IL-17F) in Peptic Ulcer in Iraqi Patients (Medico Legal Update, 2020)
A peptic ulcer can be described as a condition in which there is a discontinuity in the entire thickness of thegastric mucosa. The discontinuity can also involve the submucosa, and in some cases, the deeper layers ofthe muscle wall(1). Immunological serological and molecular factors play a great role in the susceptibilityand diagnosis of this disease. IL-17F genotyping were reported to have an influencing in all types of pepticulcer. The current study aims to detect some cytokine concentration (proinflammatory and Regulatory) inpatients’ blood, and some cytokine polymorphism. During the time from July 2019 to November 2019,the case-control study enrolled 318 blood samples collected from the patients who attended the MarjanTeaching Hospital- Hilla, as well as 60 healthy people. IL-17F genotyping was performing for 55 patientswith peptic ulcer, and 30 healthy people as control, by using the PCR-SSP method. All types of peptic ulcerswere significantly associated with IL-17F. Associations were also observed with IL-12A and IL-CXCR2.In conclusion, IL-17F, haplotypes, and genotypes have related to peptic ulcers so it can be dependent as agenetic marker for the susceptibility of this disease in Iraq